Natural killer cells- from innate cells to the discovery of adaptability - Basílio-Queirós, Débora; Mischak-Weissinger, Eva (Frontiers in Immunology, 2023)
Natural Killer (NK) cells have come a long way since their first description in the 1970's. The most recent reports of their adaptive-like behavior changed the way the immune system dichotomy is described. Adaptive NK cells present characteristics of both the innate and adaptive immune system. This NK subpopulation undergoes a clonal-like expansion in response to an antigen and secondary encounters with the same antigen result in an increased cytotoxic response. These characteristics can be of extreme importance in the clinical setting, especially as adoptive immunotherapies, since NK cells present several advantages compared other cell types. This review will focus on the discovery and the path to the current knowledge of adaptive NK cells population.